Physicochemical and Bacteriological Analyses of Groundwater in the Periphery of the Bagmati River in Kathmandu Valley - Silwal, Sandhya; Shrestha, Sanjiv; Shrestha, Soniya; Khatiwada, Manisha; Jaishi, Anita (Kathmandu University Journal of Science, Engineering and Technology, 2020)
The objective of this study was to assess the physicochemical and bacteriological quality of groundwater samples. A total of 34 samples were taken during the time period of June 6 to June 21 of 2016 from the groundwater sources in Kathmandu, located in the periphery of Bagmati river, from Chobhar to Sinamangal with approximate distance of 10 km. Site for study, sample collection, transportation, preservation and processing (bacteriological and physicochemical analyses) of samples were carried out following standard protocols issued by [1, 2]. Membrane filtration technique was employed for enumeration of indicator organism (coliform and thermotolerant coliform) and biochemical tests for its identification.The temperatures of water sample ranged from 19.6°C to 24.6°C and pH from 6.9 to 7.8 during early afternoon of different sampling days. Electrical conductivity (EC) varied from 20 µS/cm to 890 µS/cm showing a positive correlation with the Total Dissolved Solids (TDS) values. The samples were found to contain higher turbidity that ranged from 5 NTU to 14 NTU. The Dissolved Oxygen (DO) values were within the WHO limit, ranging from 5 mg/L to 7.9 mg/L. The water samples did not have problems regarding the chloride, nitrate or phosphate levels. The levels of ammonia and iron were found to be higher than the standard values. Out of 34 samples, only three samples (9%) were coliform free and the rest of the samples showed contamination. Escherichia coli (E. coli) isolates were obtained from six of the samples (18%), ranging from 2 cfu/100 mL to 5 cfu/100 mL. Thus, 31 samples were found to be unfit for drinking having tested positive for coliforms. Overall, samples from Chobhar to Balkhu, specifically nearby Manjushree area were found to have better quality than other water samples but still none of the samples have unquestionable quality.